Improvement of natamycin production by controlling the morphology of Streptomyces gilvosporeus Z8 with microparticle talc in seed preculture. Issue 6 (2nd February 2021) - Yue, Chaoping; Xu, Haitao; Yu, Yingying; Yu, Xin; Yu, Min; Zhang, Chen; You, Qian; Xia, Shaofan; Ding, Zixian; Fu, Hao; Zeng, Xin; Li, Feng
Abstract: BACKGROUND: Natamycin, an antifungal agent, has been widely used as a food preservative and medicine for fungal disease therapy. Seed preculture plays a crucial role in natamycin production, while studies on the effects of seed morphology on natamycin biosynthesis and corresponding regulation approaches are still absent. RESULTS: Correlation analyses among spore age, seed morphology and natamycin production showed that old spores tended to form larger mycelial pellets, which gave rise to a significant reduction of natamycin biosynthesis. To solve this problem, microparticle talc was added to regulate the mycelial morphology in seed preculture. Optimal talc addition led to small mycelial pellets with hairy superficial mycelia and loose structure, resulting in higher glucose‐6‐phosphate dehydrogenase activity and energy charge. The seed morphology regulation effectively improved the natamycin titer and decreased the culture time, especially for old spores (age 28 days), with a 1.7‐fold higher natamycin titer and 16.9% culture time reduction. Unfortunately, direct talc addition proved to be infeasible for natamycin fermentation in a 5 L fermentor, which was attributed to physical damage from rapid agitation and excessive talc crashing. Therefore, the morphology engineering strategy was preferred in the seed preculture process rather than formal fermentation for natamycin production. CONCLUSION: The new strategy proposed in this study could not only improve natamycin production, but also reduced the culture time. Furthermore, this work could provide references for other biochemicals production by filamentous bacteria or fungi, which would be of great significance in industrial antibiotic fermentation. © 2021 Society of Chemical Industry